Microsoft SharePoint Foundation 2010 : step by step - Londer, Olga M. (Step by step (Redmond, Wash.), 2011)
A guide to Microsoft SharePoint Foundation 2010 covers such topics as setting up a team site, capturing and organizing content into libraries, using blogs and wikis, and automating business processes.